Pengaruh Strategi Systematic Approach to Problem Solving terhadap Hasil Belajar Agama Islam Siswa Kelas IV SDN Tengah 01 Pagi Jakarta Timur - A Arifannisa (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2017)
This study aims to kind of effect a systematic approach to problem solving strategy against Islamic learning outcomes for elementary school students grade 4 in Central SDN 01 Pagi, East Jakarta. This study uses quasy Experimental Design, which takes nonequivalent control group design method. Quasy experiment design has the control group but can not interfere excution of the experimental group. Each instrument has a goal 25 tests with four possible answers. The validity of the test is calculated by product moment correlation. Reliability test is calculated by the KR-21. This research was conducted at SDN 01 Pagi Middle East Jakarta in 4 grade. The population consists of 71 students. Samples using saturated sample consisted of 71 students from the IVA has 35 students and IV B has 36 students. From the results, it can be concluded that a systematic approach to problem solving strategies affect the learning outcomes of Islamic religious education for elementary school students grade 4 in Central SDN 01 Pagi.